THE GEOPOLITICAL LANDSCAPE OF THE WORLD (American Journal of Interdisciplinary Research and Development, 2023)
This article covered the field of geopolitics, which encompasses the most urgent issues of today's modern era, and the issue of modern trends, their characteristics, and factors affecting their formation.